Subway-Induced Vibration Measurement and Evaluation of the Structure on a Construction Site at Curved Section of Metro Line - Weixing Shi; Ligang Bai; Jianping Han (Shock and Vibration)
Metro property buildings developed rapidly in metropolitan cities over last several years in China. The subway-induced vibration, which may influence the serviceability of the buildings and the comfortability of their occupants over or near the metro lines, has been paid more and more attention by professional and academic experts. Based on the vibration measurement data of a construction site over Shenzhen Metro line No. 1, this paper utilizes the reasonable and completed data processing method to handle and analyse the measured data. Through the analysis of the data, the subway-induced vibration propagation trend of free field along the perpendicular direction to metro line was investigated. It is demonstrated that the subway-induced vibration propagation along the perpendicular direction to metro line was damped out on free field as a whole. But there may exist “rebound phenomenon” at local zones. The responses on pile top and soil adjacent to pile in the vertical shaft along three directions were investigated, and their characteristics in time and frequency domains are compared. Comparison indicates that the subway-induced vibration on pile top is stronger than soil site near the pile. The measurement results on free field reveal that the most obvious feature of this metro line with curved section is that the vibration along the perpendicular direction is stronger than the other directions. But the measurement results in the vertical shaft show that the vertical vibration mainly transferring through the pile and pile’s vibration in the vertical direction is dominant. Finally, the dynamic time-history analysis of the building model under the measured acceleration was conducted. The analytical results show that the vibration response of two evaluation indicators increases with the decrease of damping ratio along all three directions. The vertical vibration is more dominant than other two directions at each floor of building. The vibration levels decrease with the increase of story number along vertical direction and firstly decrease and then increase with the increase of story number increasing along two lateral directions.